P191 With A Low Incidence Of Drug-induced Hepatitis, Should We Be Offering Latent Tb Treatment To More Patients Over The Age Of 35?. (10th November 2014) - Howlett, P; Lungu, N; Owen, W; Breen, R; Baker, L
Abstract : Introduction: NICE guidelines recommend patients >35 yrs at risk of tuberculosis (TB) on screening, but without active disease, should not be offered latent TB infection (LTBI) treatment unless a healthcare worker, or HIV positive. This is based on perceived risks of drug-induced hepatitis, and reduced diagnostic sensitivity of LTBI in >35's. 3 months Rifampicin/Isoniazid (3RH) is commonly used however in a review of LTBI treatment, only one Hong-Kong based study found 1766/100, 000 (n = 170) had symptomatic hepatitis or alanine aminotransferase (ALT) >250 IU (Grade 3 hepatitis). 1 Prompted by improved sensitivity of LTBI case finding with interferon gamma testing, and local case of active TB in a contact >35 yrs, we studied whether those >35 yrs with LTBI, treated with 3RH experienced greater hepatotoxicty than Method: We retrospectively analysed electronic patient records detailing LTBI patient treatments from June 2008–2013 from two hospitals, collecting baseline clinical data and ALT level >2 weeks into treatment. Results: Of 270 eligible patients, 151 had complete results and were included. 98/151 (65%) were 35 yrs (range 35–75), of whom 32 (60%) were male. Only 3 patients (2 males) developed ALT >250 IU/L (rate of 1, 987/100, 000), all patients were symptomatic and required treatment cessation. Ages were 31, 32 and 52 yrs and the single female patient was pregnant starting treatment. None required admission and all liver function returned to normal following cessation. Discussion: This study, although small, provides a similar rate of hepatitis (defined >250 IU/L or symptoms) to the only previous study using the 3RH regimen and shows no age specific differences in ALT results. In light of this, we raise the question; with increasing rates of TB in the UK, a large proportion of which is attributable to latent infection, should we be offering LTBI treatment to more patients >35 yrs? This study suggests the need, and provides important information for, planning a larger study to help answer this question. Reference: Ormerod et al . BTS recommendations for assessing risk and for managing Mycobacterium tuberculosis infection and disease in patients due to start anti-TNF-a Thorax 2005;60:800–805